The Effect of Iron-Containing Powders on Chemical Compositions of Oils; Procedia Chemistry; Vol. 15 : Chemistry and Chemical Engineering in XXI century (CCE 2015) - Golushkova E. B. Evgeniya Borisovna (2015, 2015)
Title screen